The philosophy of science fiction film - Sanders, Steven, 1945- (Philosophy of popular culture., 2008)
The science fiction genre maintains a remarkable hold on the imagination and enthusiasm of the filmgoing public, captivating large audiences worldwide and garnering ever-larger profits. The Philosophy of Science Fiction Film explores the storylines, conflicts, and themes of fifteen science fiction film classics, from Metropolis to The Matrix. Editor Steven M. Sanders and a group of outstanding scholars in philosophy, film studies, and other fields raise science fiction film criticism to a new level by penetrating the surface of the films to expose the underlying philosophical arguments, ethical perspectives, and metaphysical views. Sanders's introduction presents an overview and evaluation of each essay and poses questions for readers to consider as they think about the films under discussion.